2008
DOI: 10.1037/a0012948
|View full text |Cite
|
Sign up to set email alerts
|

The MMPI-2 Restructured Clinical Scales in the assessment of posttraumatic stress disorder and comorbid disorders.

Abstract: This study examined the psychometric properties of the Minnesota Multiphasic Personality Inventory-2 (MMPI-2) Restructured Clinical Scales (RCSs) in individuals with posttraumatic stress disorder (PTSD) receiving clinical services at Veterans Affairs medical centers. Study 1 included 1,098 men who completed the MMPI-2 and were assessed for a range of psychological disorders via structured clinical interview. Study 2 included 136 women who completed the MMPI-2 and were interviewed with the Clinician Administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
41
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 62 publications
12
41
0
Order By: Relevance
“…The low pathology group overall showed the least amount of elevation. These findings regarding both the PSY-5 and RC scales are consistent with previous research on these personality types, showing similar elevations and levels on each domain (see Miller et al, 2004;Wolf et al, 2008).…”
Section: R E S U L T S Personality Groupssupporting
confidence: 91%
“…The low pathology group overall showed the least amount of elevation. These findings regarding both the PSY-5 and RC scales are consistent with previous research on these personality types, showing similar elevations and levels on each domain (see Miller et al, 2004;Wolf et al, 2008).…”
Section: R E S U L T S Personality Groupssupporting
confidence: 91%
“…Scale PK showed marked correlations with avoidance and arousal symptoms and correlated moderately with intrusive symptomatology. These findings correspond to results reported by Wolf et al (2008).…”
Section: Discussionsupporting
confidence: 96%
“…With respect to SNAP trait and temperament scale associations with PTSD, this study demonstrated that negative temperament shares the most variance with overall PTSD severity, following prior work with other measures of personality (e.g., Clark, Watson, & Mineka, 1994; Clark & Watson, 1991; Miller, 2003; Wolf et al, 2008). The finding that this scale evidenced associations with all four PTSD symptom clusters highlights the contribution of non-specific distress to the disorder, a phenomenon which is not unique to the SNAP and replicates prior work showing associations between NEM and PTSD symptoms broadly (Marshall, Schell, & Miles, 2010; Wolf et al, 2008).…”
Section: Discussionsupporting
confidence: 63%
“…With respect to SNAP trait and temperament scale associations with PTSD, this study demonstrated that negative temperament shares the most variance with overall PTSD severity, following prior work with other measures of personality (e.g., Clark, Watson, & Mineka, 1994; Clark & Watson, 1991; Miller, 2003; Wolf et al, 2008). The finding that this scale evidenced associations with all four PTSD symptom clusters highlights the contribution of non-specific distress to the disorder, a phenomenon which is not unique to the SNAP and replicates prior work showing associations between NEM and PTSD symptoms broadly (Marshall, Schell, & Miles, 2010; Wolf et al, 2008). Although there is a conceptual appeal to attempts to remove NEM-related variance from the PTSD criteria so that only disorder-specific variance is retained (Simms, Watson, & Doebbeling, 2002; Watson, 2005, 2009), these results, in concert with prior work (e.g., Marshall et al, 2010), raise questions about whether this distinction is possible or clinically useful.…”
Section: Discussionsupporting
confidence: 63%